Media education in action.Models, tools and examples of good practice - Parola, Alberto; Ranieri, Maria (Anàlisi, 2013)
Currently, Media Education (ME) can no longer be considered as a field of study reserved for communication researchers, or as a privileged practice of some teachers. On the one hand, ME is now part of the agenda of international organizations, which considers the development of media skills as a prerequisite to exercise full citizenship in today's society. On the other hand, ME practices are becoming more widespread in schools and involve an increasing number of teachers. However, the teaching of the media still seems to be a fairly solipsistic, where "everything is fine". In fact, there is a tremendous lack of research on the quality and effectiveness of educational practices. In its educational dimension, the On Air project attempts to address these problems by providing a set of tools to design, develop and evaluate ME activities in schools. This paper presents and analyzes the results paying attention to the overall structure of the research and its main findings.